Lions select larger prey in a Central African protected area with increasingly effective management - Chiara Fraticelli; Abdoulaye Abakar Zayed; Herwig Leirs; Hans Bauer (Ecology and Evolution, 2024)
Abstract Lions and their prey are threatened across most of their range and especially in West and Central Africa. Prey availability influences carnivore densities, social structure, prey preference and home ranges, and changes in prey are important for carnivore management. Scarcity of large prey in many West and Central African ecosystems has been described as leading to a preference for hunting smaller prey in smaller groups. Here we investigated the changes in prey selection of lions in Zakouma National Park (Chad), a protected area in Central Africa that showed significant recovery in wildlife numbers, by collecting feeding data through observations of lions on kills during monitoring drives and GPS cluster points of lion collars. Compared to similar data collected prior to this significant recovery, lions preferred larger prey and fed in larger groups. Our results show that diet shifts due to prey losses can be reversed with restoration of prey populations thanks to improved management, and we speculate that this may be true across large carnivores and across regions.